2022
DOI: 10.3390/nu14020376
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Patterns of Glucagon and Its Relationships with Glucose and Insulin following Ingestion of Different Classes of Macronutrients

Abstract: Background: glucagon secretion and inhibition should be mainly determined by glucose and insulin levels, but the relative relevance of each factor is not clarified, especially following ingestion of different macronutrients. We aimed to investigate the associations between plasma glucagon, glucose, and insulin after ingestion of single macronutrients or mixed-meal. Methods: thirty-six participants underwent four metabolic tests, based on administration of glucose, protein, fat, or mixed-meal. Glucagon, glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…The insulin and glucagon response to an oral challenge is subject to other influences such as gastric emptying and incretin hormone release (Vella & Camilleri, 2017). However, Gobl et al recently reported that glucagon secretion after different nutrient challenges is independent of integrated insulin concentrations (Gobl et al, 2022) in keeping with data from our group (Sharma et al, 2018) and that of others (Faerch et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…The insulin and glucagon response to an oral challenge is subject to other influences such as gastric emptying and incretin hormone release (Vella & Camilleri, 2017). However, Gobl et al recently reported that glucagon secretion after different nutrient challenges is independent of integrated insulin concentrations (Gobl et al, 2022) in keeping with data from our group (Sharma et al, 2018) and that of others (Faerch et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it has been reported that glucagon has a direct potentiating effect on insulin secretion, somehow similar to the well-known effect of GLP-1, with whom glucagon shares its precursor [ 99 ]. On the other hand, it is becoming evident that insulin control on glucagon secretion and kinetics may be even more marked than glucose control [ 100 , 101 ], and several other factors have also been suggested as modulators of glucagon secretion, such as insulin-like growth factor-1, apolipoprotein A-1, and HDL cholesterol [ 102 , 103 ]. In addition, it is now clear that the alpha cell exerts effects on the maintenance of glucose homeostasis that are beyond the effects related to glucagon.…”
Section: Discussionmentioning
confidence: 99%
“…This variation in glucagon secretion in response to food intake might be attributed to the different compositions of carbohydrates, proteins and lipids in various foods. Although there have been several reports examining glucagon responses to macronutrient intake 3 , 4 , 5 , 6 , 7 , 8 , there have been arguments regarding the accuracy of glucagon measurement, as glucagon secretion was evaluated by conventional radioimmunoassay in most studies 3 , 4 , 5 . Furthermore, very few reports to date have investigated glucagon responsiveness to glucose, protein and lipid in a single study 4 , 6 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been several reports examining glucagon responses to macronutrient intake 3 , 4 , 5 , 6 , 7 , 8 , there have been arguments regarding the accuracy of glucagon measurement, as glucagon secretion was evaluated by conventional radioimmunoassay in most studies 3 , 4 , 5 . Furthermore, very few reports to date have investigated glucagon responsiveness to glucose, protein and lipid in a single study 4 , 6 , 8 . To properly investigate the fluctuations of glucagon secretion after the intake of each nutrient, plasma glucagon profiles were measured using a sandwich‐type enzyme‐linked immunosorbent assay method after the intake of carbohydrates, proteins or lipids, separately, in 10 Japanese people without diabetes.…”
Section: Introductionmentioning
confidence: 99%